A Year of Bad Choices: The Postfeminist "Restorying" of Teen Dating Violence in Young Adult Literature. (August 2017) - Storer, Heather L.
Teen dating violence (TDV) is a significant social justice issue. The prevention of TDV requires interventions across ecological systems levels including the macro-level. The media has been implicated as influencing societal-level narratives about TDV. Using critical discourse analysis methodology, the purpose of this study is to unpack the dominant cultural narratives about TDV in young adult (YA) literature, a media genre that is marketed to adolescents. Data include YA novels with a central focus on TDV ( n = 8). Through these novels, the language of gender inequality was supplanted by a postfeminist rhetoric of choice, personal responsibility, and self-help.